2016
DOI: 10.1002/vnl.21544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maleated polypropylene as a compatibilizer and hyperbranched polyester as a processing aid on polypropylene‐wood flour biocomposites

Abstract: This work focused on two difficulties associated with preparation of polypropylene/wood flour (PP/WF) composites, viz. the compatibility of PP with WF and processing of the composites with high melt viscosity. Maleic anhydride-grafted polypropylene (MAPP) was used in the preparation of PP composites to provide the compatibility between polymer and filler. Hyperbranched polyester (HBPE) was incorporated to check feasibility of it as a processing aid in the same. The PP/WF composites were formulated by melt comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The increase in IFSS was because of the co-polymer character of MAPP sizing. The hydrophilic anhydride groups of the sizing reacted with the hydroxyl groups on the CF surface, while the hydrophobic PP section was compatible with the PP matrix molecules [ 26 ]. This resulted in a stronger interfacial interaction and thus stronger adhesion with the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in IFSS was because of the co-polymer character of MAPP sizing. The hydrophilic anhydride groups of the sizing reacted with the hydroxyl groups on the CF surface, while the hydrophobic PP section was compatible with the PP matrix molecules [ 26 ]. This resulted in a stronger interfacial interaction and thus stronger adhesion with the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…There are various successful compatibilizing methods that have shown good improvement in the mechanical and thermal properties, as a result of interphase modifications. One recent approach for compatibilization was done by Nevare et al where they studied the effect of maleated polypropylene (PP) as a compatibilizer and hyperbranched polyester as a processing aid on PP/wood flour biocomposites [12]. Compatibilization with biobased polymers was done by Ferrer et al and in that they studied the reinforcement of PP with lignocellulose nanofibrils [13].…”
Section: Introductionmentioning
confidence: 99%
“…Of the interfacial compatibilizers, the graft copolymers are an excellent compatibilizers for WPC. [11][12][13] But the loadings of compatibilizers result in the complex variation of rheological properties of the composites by changing the interfacial interactions. [14][15][16] Several previous reports have shown that the rheological properties of WPCs were significantly affected by the interfacial interactions of the composites.…”
Section: Introductionmentioning
confidence: 99%